Negative Impact of Noise Exposure on the Mean Number of Neurons in the Frontal Lobe of Adult Wistar Rats - Evayanti, Luh Gde; Astini, Dewa Ayu Agung Alit Suka; Sumadewi, Komang Trisna; Witari, Ni Putu Diah; Wijaya, Putu Austin Widyasari; Ekayanti, Ni Wayan Sri; Ekayani, Ni Wayan Diana (Jambura Medical and Health Science Journal, 2026)
Introduction: Noise exposure can induce oxidative stress and alter neurotransmitter dynamics within the nervous system. This oxidative stress is also associated with structural changes in the layers of the cerebrum. However, the effects of noise exposure on neuronal populations remain inadequately understood. This study aims to quantify the mean number of neurons in the frontal lobe of Wistar rats subjected to noise exposure.Methods: This study utilized an experimental design characterized by a randomized post-test only control group framework. A total of 30 male Wistar rats were selected through simple random sampling and subsequently divided into two groups: a control group without treatment (C1, n=15) and an experimental group exposed to 95 dB noise (E1, n=15) for four hours daily. Following a two-week exposure period, their brain tissue was excised and preserved in 10% neutral buffered formalin. Histological assessment was conducted using Hematoxylin and Eosin staining to evaluate the mean number of neurons in the frontal lobe. Statistical analysis was performed using the independent T-test.Results: The mean number of neurons was 1053.33 ± 55.529 in the E1 group and 720.167 ± 61.135 in the C1 group. The mean neurons of the frontal lobe of Wistar rats in the E1 group ws lower than the C1 group significantly (P 0.001).Conclusion: Neuronal death in the frontal lobe resulting from noise-induced stress can induce structural alterations within this region, leading to detrimental effects on cognitive function and behavior. Keywords: Frontal lobe, neuron, noise, stress